Using Microsoft PowerPoint 2002 - Rutledge, Patrice-Anne (Special Edition Using Ser., 2001)
Special Edition Using Microsoft PowerPoint 2002 is created for experienced users who want to be able to use PowerPoint's more sophisticated features, as well as its basic ones. Because creating successful presentations is more than just becoming a PowerPoint power user, included is a special section in the book on presentation skills. With the addition of this special section, it makes this title uniquely different from all other titles out in the marketplace. Topics covered include: Working with tables Collaborating on presentations Working with speech tools Adding movies and sound Working with PowerPoint in the Web Creating macros Creating and editing Web scripts